EFFECT OF DIFFERENT SALINITY ON GROWTH AND SURVIVAL RATE OF NILE TILAPIA (Oreochromis niloticus) - Ridho Dian Prayudi; Rusliadi '; Syafriadiman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from 23 March to 22 April 2015 that held atthe Great Hall Brackishwater Aquaculture Development Jepara, Central JavaProvince. The aim of this research to determine the different salinity for growthand survival rate of nile tilapia (Oreochromis niloticus). The method used is theexperimental method with completely randomized design (CRD) of the factorwith 4 levels a treatment. The treatment was applied, namely P1 of salinity 10 ppt,P2 of salinity 12 ppt, P3 of salinity 14 ppt and P4 of salinity 16 ppt with 3 timesrepetition.The results showed different salinity 10, 12, 14 and 16 ppt did not give asignificant effect (P>0,05) on the total absolute body weight, absolute bodylength, daily growth rate and survival rate of nile tilapia. The best treatmentcontained in P3 (14 ppt) with absolute body weight 2,46 g, absolute body length3,35 cm and the specific growth rate of 6,30 %. The best treatment of survival rateon 12 (78,67 %) and 16 (78,67 %).Keywords: Western white prawns, Salinity , Growth, Survival Rat